1953
DOI: 10.1113/jphysiol.1953.sp004859
|View full text |Cite
|
Sign up to set email alerts
|

The role of acetylcholine in synaptic transmission at parasympathetic ganglia

Abstract: It has usually been assumed, since the suggestion made by Dale (1933), that transmission at the parasympathetic ganglionic synapse is cholinergic, but proof of the validity of the assumption is difficult for two reasons. In the first place most parasympathetic ganglion cells are diffusely scattered throughout effector tissues and are not, as are sympathetic ganglion cells, congregated in anatomically recognizable ganglia; only three recognizable ganglia of the parasympathetic system are known, the ciliary, oti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

1954
1954
1979
1979

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…The sensitization of the ganglion cells to the action of ACh produced by glycosides is very similar to the sensitization produced in denervated ganglia by the methonium compounds (Perry and Reinert, 1954b), which is probably associated with the transfer of potassium ions across the cell membrane. Thus, the failure of the glycosides to exert their sensitizing effect in the absence of external potassium may be significant, in that the action of ouabain may render the cell membrane more permeable to potassium ions, thus enhancing the effect of ACh.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…The sensitization of the ganglion cells to the action of ACh produced by glycosides is very similar to the sensitization produced in denervated ganglia by the methonium compounds (Perry and Reinert, 1954b), which is probably associated with the transfer of potassium ions across the cell membrane. Thus, the failure of the glycosides to exert their sensitizing effect in the absence of external potassium may be significant, in that the action of ouabain may render the cell membrane more permeable to potassium ions, thus enhancing the effect of ACh.…”
Section: Discussionsupporting
confidence: 48%
“…The block of small doses of ACh produced by hexamethonium was interpreted by Perry and Talesnik (1953) as implying that these doses of ACh produced their action by stimulating the vagal ganglion cells and not the myocardium. In support of this contention they showed that hexamethonium did not exert any blocking action to the effect of stimulation of the post-ganglionic parasympathetic fibres supplying the pupil.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations